Effect of five non-invasive treatments on body composition, physical function and quality of life in elderly sarcopenia: a network meta-analysis of 22 randomized controlled trials - Demin Kong; Jiangang Chen (Frontiers in Physiology)
IntroductionWhile exercise interventions are widely used for sarcopenia management, the comparative efficacy of different non-invasive treatments remains unclear. This network meta-analysis evaluated five interventions (aerobic training, resistance training, aerobi-resistance training, whole-body electrical stimulation, and electrical stimulation with protein supplementation) on body composition, physical function and quality of life in elderly sarcopenia patients.MethodsSix databases, including PubMed, Embase and Web of Science, were systematically searched, and 22 randomized controlled trials with a total of 1062 elderly patients with sarcopenia were finally included. The outcome indicators were those related to the evaluation of body composition, physical function and quality of life. Net meta-analysis was performed using Stata 17.0 to assess the relative effectiveness of each intervention and to test the consistency of direct and indirect evidence.ResultsES&P (SMD = −3.33, 95% CI [−4.23, −2.44], p < 0.00001) and AT (SMD = −1.31, 95% CI [−1.83, −0.79], p < 0.00001, I2 = 58%) demonstrated significant effects in terms of fat reduction, RT achieved a significant effect in terms of muscle gain (SMD = 0.50, 95% CI [0.08, 0.91], p < 0.05, I2 = 42%), RAT was the most effective in terms of strength gains (SMD = 0.51, 95% CI [0.05, 0.98], p < 0.05, I2 = 0%), and RAT also demonstrated a favorable effect in terms of improving quality of life (SMD = 1.42, 95% CI [0.13, 2.70], p < 0.05, I2 = 55%).ConclusionES & P and AT have good effect on fat reduction, RT has the best effect on increasing muscle, RAT is the most effective in improving strength, and AT is the best in improving quality of life. Different treatments have different effects on functional indicators, and clinics should personalize the selection of different interventions according to the patient’s condition and combine multiple interventions to achieve the best recovery results.